Hawk - Patterson, James, 1947-; Charbonnet, Gabrielle (Patterson, James, 1947. Hawk, 2020)
Maximum Ride's seventeen-year-old daughter, Hawk, is living under the radar in post-apocalyptic New York City until a destiny that is perilously close to her mother's forces her to take flight.